2022
DOI: 10.1136/jnis-2022-019153
|View full text |Cite
|
Sign up to set email alerts
|

Intrasaccular flow disruption for ruptured aneurysms: an international multicenter study

Abstract: BackgroundThe Woven EndoBridge (WEB) device is a novel intrasaccular flow disruptor tailored for bifurcation aneurysms. We aim to describe the degree of aneurysm occlusion at the latest follow-up, and the rate of complications of aneurysms treated with the WEB device stratified according to rupture status.MethodsOur data were taken from the WorldWideWeb Consortium, an international multicenter cohort including patients treated with the WEB device. Aneurysms were classified into two groups: ruptured and unruptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…21,22 However, the meta-analysis by Asnafi et al 8 demonstrated similar midterm AO rates between ruptured and unruptured aneurysms, suggesting that the efficacy of WEB treatment may not significantly differ based on the rupture status of the aneurysm. Similarly, Diestro et al 23 reported a comparable AO rate in unruptured aneurysms to our data (94.4%), whereas the rate for ruptured aneurysms was 83.3%, but this difference was not statistically significant (P = .066). Overall, existing literature supports the high safety and efficacy of WEB treatment for WIBAs in the short and mid term.…”
Section: Discussionsupporting
confidence: 63%
“…21,22 However, the meta-analysis by Asnafi et al 8 demonstrated similar midterm AO rates between ruptured and unruptured aneurysms, suggesting that the efficacy of WEB treatment may not significantly differ based on the rupture status of the aneurysm. Similarly, Diestro et al 23 reported a comparable AO rate in unruptured aneurysms to our data (94.4%), whereas the rate for ruptured aneurysms was 83.3%, but this difference was not statistically significant (P = .066). Overall, existing literature supports the high safety and efficacy of WEB treatment for WIBAs in the short and mid term.…”
Section: Discussionsupporting
confidence: 63%
“…The retreatment rate was significantly higher in the ruptured versus the unruptured group (13% vs 3.9%, respectively, P<0.0001). However, since multiple analysis5 18–20 found no statistical association between recurrence and ruptured aneurysm, we can hypothesize that operators were more prompt to treat initially ruptured recurrences, assuming a higher re-rupture risk. Similar observations have been made concerning aneurysms initially treated with coils in some series 15…”
Section: Discussionmentioning
confidence: 89%
“…After deployment in the aneurysm sac, the device provides immediate flow disruption, leading to aneurysm thrombosis and endothelialization across the aneurysm neck over time. Because the device leaves the parent artery unaffected, long-term antiaggregant therapy is not necessary ( 51 ). Several previous landmark studies, including WEBCAST, WEBCAST-2, WEB-IT, and the French Observatory, have confirmed the safety and efficacy of the WEB device ( 52–56 ).…”
Section: Various Evt Techniquesmentioning
confidence: 99%
“…For EVT for intracranial ICA bifurcation region aneurysms, a good clinical outcome can be defined as a modified Rankin scale (mRS) score ≤2 or a Glasgow Outcome Scale (GOS) score of 4 or 5 ( 74 , 75 ). Angiographic aneurysm occlusion after traditional coiling or WEB device deployment can be assessed by the Raymond–Roy occlusion scale (RROS) ( 51 , 76 ). Adequate angiographic outcomes of aneurysm occlusion were defined as RROS class I (complete occlusion) or class 2 (near complete occlusion with a small residual neck).…”
Section: Prognosis and Complicationsmentioning
confidence: 99%